UPAYA MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR MATEMATIKA MELALUI PENERAPAN METODE PERMAINAN SISWA KELAS V MIN 13 NGAWI - Weni Puji Astutik (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
Mathematics learning involves interaction between students and teachers, incorporating various components to achieve educational goals. One of the topics taught is Geometry and Measurement, particularly understanding the concept of object weight. However, many students struggle with word problems, unit conversions, and lack interest due to monotonous teaching methods. This results in low learning engagement and academic performance, failing to meet the competency standards at MIN 13 Ngawi. To address these challenges, an innovative teaching approach is needed, such as implementing the buying and selling game method. This method utilizes tangible objects, such as play money, scales, and trade goods, allowing students to grasp concepts through hands-on experiences. Through this simulation, students actively participate, enhance their learning motivation, and develop critical thinking skills. The implementation of this method is expected to create a more engaging learning environment, increase student involvement, and improve mathematics learning outcomes.